Fall Prevention in Community Settings: Results from Implementing Tai Chi: Moving for Better Balance in Three States - Ory, Marcia G.; Smith, Matthew Lee; Parker, Erin M.; Jiang, Luohua; Chen, Shuai; Wilson, Ashley D.; Stevens, Judy A.; Ehrenreich, Heidi; Lee, Robin (Frontiers in Public Health, 2015)
.